Application of SiO2 / C composite material in tire high-thermal-conductivity base rubber
By using SiO2/C composite material in the high-thermal conductivity base glue of tires, the carbonization of edible fungi and porous silica is used to form a thermal conductivity channel, the problems of poor thermal conductivity and insufficient dispersion of white carbon black are solved, and low heat generation and high The effect of thermal conductivity is taken into account.
Patent Information
- Application Number
- CN202411393976.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-08
AI Technical Summary
While reducing the rolling resistance, the poor thermal conductivity of white carbon black leads to high heat generation and easy damage, and the dispersion and reinforcement performance of white carbon black are insufficient.
SiO2/C composite material is used in the tire high-thermal conductivity base glue, and a highly dispersible SiO2/C aggregate is formed by carbonizing edible fungi and porous silica, which enhances the thermal conductivity of carbon black and improves thermal conductivity and dispersion.
It achieves low heat generation while improving the thermal conductivity of the tire, solving the problems of poor thermal conductivity and insufficient dispersion of white carbon black. The prepared tires have better thermal conductivity and reinforcement effects.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tire base rubber, and in particular to application of a SiO2 / C composite material in a tire high thermal conductivity base rubber. Background Art
[0002] In order to reduce rolling resistance, green tires have been using high-quality white carbon black to solve the problem of low hysteresis in recent years. The surface polarity of white carbon black is strong and difficult to disperse. In order to solve the dispersion problem of white carbon black, white carbon black has been modified in recent years, especially silane modification has achieved very good results, and the prepared tires have low heat generation. However, white carbon black has poor thermal conductivity. Although the heat generation is low, the heat generated by the tire cannot be conducted away, resulting in high accumulated heat generation of the tire, which makes the tire easy to damage. Therefore, it is very important to develop low heat generation and high thermal conductivity fillers to solve the low heat generation and high thermal conductivity of the base rubber, which is also a major problem in the industry. Summary of the invention
[0003] The purpose of the present invention is to overcome the defects in the prior art and provide an application of a SiO2 / C composite material in a high thermal conductivity base rubber of a tire.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides an application of a SiO2 / C composite material in a high thermal conductivity base rubber for a tire, wherein the high thermal conductivity base rubber for a tire comprises the following raw materials in parts by mass:
[0006] 90-110 parts of natural rubber, 0-45 parts of filler, 10-45 parts of SiO2 / C composite material, 4-10 parts of activator, 2-5 parts of vulcanizer, 2-5 parts of antioxidant, and 0.5-1.5 parts of microcrystalline wax.
[0007] Preferably, the filler is one or more of carbon black N220, carbon black N234, carbon black N375, carbon black N347, carbon black N339, carbon black N330, carbon black N326, carbon black N660 and pyrolysis carbon black.
[0008] Preferably, the method for preparing the SiO2 / C composite material comprises the following steps:
[0009] (A), mixing the edible fungus cultivation body with porous silica to obtain a silica composite edible fungus cultivation body;
[0010] The silicon dioxide composite edible fungus cultivation body is mixed with edible fungi to culture the edible fungi; after the culture is completed, the edible fungi are removed and the discarded cultivation body is retained;
[0011] (B) Carbonizing the discarded culture medium in step (A) to obtain a SiO2 / C composite material.
[0012] Preferably, the porous silica is one or more of silica powder, carbon fiber, diatomaceous earth, diatomaceous shale, opal, zeolite and montmorillonite.
[0013] Preferably, the activator is one or more of stearic acid, zinc oxide, zinc stearate and lignin zinc salt.
[0014] Preferably, the vulcanizing agent is one or more of sulfur, accelerator NS and accelerator CZ; the antioxidant is antioxidant 4020 and / or antioxidant RD.
[0015] Preferably, the method for preparing the tire high thermal conductivity base rubber comprises the following steps:
[0016] (1) mixing natural rubber, filler, SiO2 / C composite material, activator, antioxidant and microcrystalline wax to obtain a masterbatch;
[0017] (2) The masterbatch and the vulcanizing agent are mixed to obtain the tire high thermal conductivity base rubber.
[0018] Preferably, the mixing speed in step (1) is 45-55 rpm, the mixing time is 30-50 s, the bolt lifting and pressing time of the mixing is 20-30 s, and the mixing debonding temperature is 145-165°C.
[0019] Preferably, the mixing speed in step (2) is 25-35 rpm; the mixing time is 30-50 s, the bolt lifting and pressing time of the mixing is 20-30 s, and the mixing debonding temperature is 100-113°C.
[0020] The present invention provides an application of a SiO2 / C composite material in a high thermal conductivity base rubber of a tire. The composite material can effectively replace white carbon black in the tire preparation process, and the prepared tire has low heat generation and high thermal conductivity. The present invention utilizes the carbonization of edible fungi and organically combines with SiO2 to form a SiO2 / C aggregate with high dispersibility, which plays a role in reducing the Payne of the filler, thereby reducing heat generation; secondly, the present invention uses a porous silica material, so that SiO2 and C are closely combined to form a heat conduction channel, which enhances the thermal conductivity of the filler and promotes the prepared rubber composition to have high thermal conductivity.
[0021] The present invention also provides a high thermal conductivity base rubber for tires, comprising 90-110 parts of natural rubber, 0-45 parts of fillers, 10-45 parts of SiO2 / C composite materials, 4-10 parts of activators, 2-5 parts of vulcanizers, 2-5 parts of antioxidants, and 0.5-1.5 parts of microcrystalline wax. The SiO2 / C composite material in the present invention is closely combined with the reinforced white carbon black and carbon black to form a heat conduction channel to solve the problems of poor thermal conductivity and static electricity of white carbon black, so that the prepared tire base rubber rubber composition has low heat generation and high thermal conductivity.
[0022] The problems that the present invention is intended to solve: the problem of poor thermal conductivity caused by the low heat generation of white carbon black used in low rolling resistance tires is solved, the SiO2 / C composite material strengthens the close combination of white carbon black and carbon black, and the carbon black is attached to the surface of the white carbon black to form a carbon black heat conduction channel, thereby solving the problem of poor thermal conductivity of white carbon black, and at the same time, the low heat generation of porous white carbon black is used to achieve lower heat generation; the attached carbon black is used to enhance the physical and chemical combination of rubber and the SiO2 / C composite material, thereby improving the reinforcement performance of the SiO2 / C composite material and solving the problem of poor reinforcement performance of white carbon black; the SiO2 / C composite material solves the dispersion problem of white carbon black, and the prepared base rubber has better low heat generation performance. DETAILED DESCRIPTION
[0023] The present invention provides an application of a SiO2 / C composite material in a high thermal conductivity base rubber for a tire, wherein the high thermal conductivity base rubber for a tire comprises the following raw materials in parts by mass:
[0024] 90-110 parts of natural rubber, 0-45 parts of filler, 10-45 parts of SiO2 / C composite material, 4-10 parts of activator, 2-5 parts of vulcanizer, 2-5 parts of antioxidant, and 0.5-1.5 parts of microcrystalline wax.
[0025] In the present invention, the mass fraction of the natural rubber is preferably 92 to 108 parts, more preferably 95 to 105 parts, and even more preferably 98 to 102 parts.
[0026] In the present invention, the mass fraction of the filler is preferably 5 to 40 parts, more preferably 10 to 30 parts, and even more preferably 15 to 25 parts.
[0027] In the present invention, the mass fraction of the SiO2 / C composite material is preferably 15 to 40 parts, more preferably 20 to 35 parts, and even more preferably 25 to 30 parts.
[0028] In the present invention, the mass fraction of the activator is preferably 6 to 9 parts, more preferably 7 to 8 parts, and even more preferably 7.3 to 7.7 parts.
[0029] In the present invention, the mass fraction of the vulcanizing agent is preferably 2.5 to 4.5 parts, more preferably 3 to 4 parts, and even more preferably 3.3 to 3.7 parts.
[0030] In the present invention, the weight percentage of the antioxidant is preferably 2.5 to 4.5 parts, more preferably 3 to 4 parts, and even more preferably 3.3 to 3.7 parts.
[0031] In the present invention, the mass fraction of the microcrystalline wax is preferably 0.6 to 1.4 parts, more preferably 0.7 to 1.3 parts, and even more preferably 0.8 to 1.2 parts.
[0032] In the present invention, the filler is one or more of carbon black N220, carbon black N234, carbon black N375, carbon black N347, carbon black N339, carbon black N330, carbon black N326, carbon black N660 and pyrolysis carbon black.
[0033] In the present invention, the preparation method of the SiO2 / C composite material comprises the following steps:
[0034] (A), mixing the edible fungus cultivation body with porous silica to obtain a silica composite edible fungus cultivation body;
[0035] The silicon dioxide composite edible fungus cultivation body is mixed with edible fungi to culture the edible fungi; after the culture is completed, the edible fungi are removed and the discarded cultivation body is retained;
[0036] (B) Carbonizing the discarded culture medium in step (A) to obtain a SiO2 / C composite material.
[0037] In the present invention, the edible fungus culture medium in step (A) preferably includes a biomass carbon source, which includes but is not limited to one or more of cottonseed hulls, corn cobs, leaf and wood chips, bean straw powder, wheat straw powder, peanut shells, bran and rice bran.
[0038] In the present invention, the source of the edible fungus culture medium in step (A) is not limited, and commercially available or non-commercially available products known to those skilled in the art can be used.
[0039] In the present invention, the porous silica in step (A) preferably includes one or more of silica lattice powder, carbon monoxide, diatomaceous earth, diatom shale, opal, zeolite and montmorillonite, and further preferably includes silica lattice powder, diatomaceous earth, diatom shale, opal, zeolite or montmorillonite, and more preferably silica lattice powder.
[0040] In the present invention, the brand of the carbon is preferably TSI-A5008.
[0041] In the present invention, the particle size of the porous silica in step (A) is preferably 500 nm to 100 μm, more preferably 500 nm to 50 μm, and more preferably 500 nm to 10 μm; the specific surface area is preferably 60 to 500 m 2 / g, more preferably 60 to 300 m 2 / g, more preferably 60 to 200 m 2 / g; the pore size is preferably 2 to 100 nm; the porosity is preferably 0.1 to 5 cm 3 / g, more preferably 0.1 to 3 cm 3 / g, more preferably 0.1 to 2 cm 3 / g.
[0042] In the present invention, the mass ratio of the porous silica to the edible fungus cultivation body in step (A) is preferably 1:1-10, more preferably 1:2-4, and even more preferably 1:2.
[0043] In the present invention, the step (A) preferably further comprises: sterilizing the silica composite edible fungus cultivation body before mixing the silica composite edible fungus cultivation body with the edible fungus.
[0044] In the present invention, the conditions for the sterilization treatment are not limited, and a method familiar to those skilled in the art can be used. Specifically, in the embodiment of the present invention, the sterilization treatment is carried out at 120° C. for 1.5 h or more.
[0045] In the present invention, the edible fungi in step (A) preferably include but are not limited to shiitake mushrooms, oyster mushrooms or black fungus. Preferably, the embodiment of the present invention takes black fungus as an example for cultivation.
[0046] In the present invention, the time to complete the culture in step (A) is preferably ≥3 months, more preferably ≥3.5 months, and more preferably 4 months.
[0047] In the present invention, step (B) preferably further comprises: naturally drying the waste culture medium in step (A) before the carbonization. The natural drying time is preferably 5 to 24 hours, more preferably 12 to 24 hours, and more preferably 24 hours.
[0048] In the present invention, the equipment used for the carbonization in step (B) is preferably a carbonization furnace.
[0049] In the present invention, in step (B), the carbonization is preferably carried out under a protective atmosphere; the protective atmosphere is preferably at least one of nitrogen or argon, more preferably nitrogen or argon, and more preferably nitrogen.
[0050] In the present invention, in step (B), the carbonization temperature is preferably 600-950°C, more preferably 700-900°C, and more preferably 800°C; the time is preferably 10-60 min, more preferably 30-60 min, and more preferably 60 min; the rate of heating to the desired carbonization temperature is preferably 5-15°C / min, more preferably 5-10°C / min, and more preferably 5°C / min.
[0051] In the present invention, the carbonization in step (B) preferably further comprises: crushing and screening in sequence.
[0052] In the present invention, the crushing equipment is preferably a planetary ball mill.
[0053] In the present invention, the crushing rotation speed in step (B) is preferably 300-700 r / min, more preferably 400-600 r / min, more preferably 500 r / min; the time is preferably 15-60 min, more preferably 20-40 min, more preferably 30 min.
[0054] In the present invention, the screening equipment is preferably a centrifugal classifier.
[0055] In the present invention, the particle size D of the sieving in step (B) is 50 It is preferably 500 nm to 45 μm, more preferably 500 nm to 20 μm, and still more preferably 500 nm to 10 μm.
[0056] In the present invention, the activator is one or more of stearic acid, zinc oxide, zinc stearate and lignin zinc salt; the lignin zinc salt is purchased from Zhongce Rubber Tire Co., Ltd.
[0057] In the present invention, the vulcanizing agent is one or more of sulfur, accelerator NS and accelerator CZ; the antioxidant is antioxidant 4020 and / or antioxidant RD.
[0058] In the present invention, the method for preparing the tire high thermal conductivity base rubber comprises the following steps:
[0059] (1) mixing natural rubber, filler, SiO2 / C composite material, activator, antioxidant and microcrystalline wax to obtain a masterbatch;
[0060] (2) The masterbatch and the vulcanizing agent are mixed to obtain the tire high thermal conductivity base rubber.
[0061] In the present invention, the mixing speed in step (1) is preferably 45-55 rpm, more preferably 46-54 rpm, and more preferably 48-52 rpm; the mixing time is preferably 30-50 s, more preferably 35-45 s, and more preferably 38-42 s; the bolt lifting and pressing time of the mixing is preferably 20-30 s, more preferably 22-28 s, and more preferably 24-26 s; the debonding temperature of the mixing is preferably 145-165°C, more preferably 150-160°C, and more preferably 152-158°C.
[0062] In the present invention, the mixing speed in step (2) is preferably 25-35 rpm, more preferably 26-34 rpm, and more preferably 28-32 rpm; the mixing time is preferably 30-50 s, more preferably 35-45 s, and more preferably 38-42 s; the bolt lifting and pressing time of the mixing is preferably 20-30 s, more preferably 22-28 s, and more preferably 24-26 s; the debonding temperature of the mixing is preferably 100-113°C, more preferably 102-110°C, and more preferably 104-106°C.
[0063] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0064] Example 1
[0065] Preparation of SiO2 / C composite materials
[0066] 2 kg of Auricularia auricula culture (from the Science and Technology Demonstration Park of Dongjingcheng Forestry Bureau, Heilongjiang) and 200 g of silica powder (D 50 -8μm, model TSI-1, manufacturer is Harbin Silicon New Materials Co., Ltd., particle size is 500nm~10μm, specific surface area is 60~200m 2 / g, pore size is 2~100nm, porosity is 0.1~2cm 3 / g) and evenly mixed to obtain a silicon dioxide composite edible fungus culture body;
[0067] After sterilizing the silica composite edible fungus culture body at 120° C. for 1.5 h, inoculating the auricularia auricula into the silica composite edible fungus culture body for cultivation, and after the auricularia auricula has been cultivated for 3 months, removing the mature auricularia auricula and retaining the discarded culture body;
[0068] The waste culture body was naturally dried for 24 hours, and then placed in a carbonization furnace, heated to 800°C at a heating rate of 5°C / min under nitrogen protection for carbonization for 60 minutes, and the carbonized silicon-carbon composite was ball-milled in a planetary ball mill at a speed of 500r / min for 30 minutes, and then the ball-milled sample was sieved by a centrifugal classifier to obtain a particle size D 50 For samples with a particle size of ≤3 μm, SiO2 / C composite materials were obtained.
[0069] Take 100 parts of natural rubber, 45 parts of SiO2 / C composite material, 6 parts of activator (2 parts of stearic acid, 4 parts of zinc oxide), 2.5 parts of antioxidant (1.5 parts of antioxidant 4020, 1 part of RD), 1 part of microcrystalline wax and 4 parts of vulcanizing agent (1 part of oil-extended 10% sulfur, 1 part of insoluble sulfur 7020, 2 parts of accelerator NS).
[0070] Put natural rubber, SiO2 / C composite material, activator, antioxidant and microcrystalline wax into an internal mixer, set the speed to 50 rpm, mix for 35 seconds, lift and press the plug to mix for 20 seconds, until the discharge temperature is 155°C, to obtain a masterbatch.
[0071] Start the internal mixer, set the speed to 30 rpm, add the masterbatch and vulcanizer, mix for 30 seconds, lift the plug and press the plug to mix for 20 seconds, until the discharge temperature reaches 105°C, and obtain the high thermal conductivity base rubber for the tire.
[0072] Example 2
[0073] The difference between Example 2 and Example 1 is that 25 parts of carbon black N330 are added and the SiO2 / C composite material is adjusted to 25 parts.
[0074] Comparative Example 1
[0075] The difference between Comparative Example 1 and Example 1 is that no SiO2 / C composite material is added, and 45 parts of white carbon black GR175 are added.
[0076] Comparative Example 2
[0077] The difference between Comparative Example 2 and Example 2 is that no SiO2 / C composite material is added, and 25 parts of white carbon black GR175 are added.
[0078] The base adhesives of Examples 1 and 2 and Comparative Examples 1 and 2 were subjected to performance tests in accordance with GB / T528-1998. The results are recorded in Table 1.
[0079] Table 1 Test results
[0080] Case Comparative Example 1 Comparative Example 2 Example 1 Example 2 Tanδ / 60℃ 0.066 0.078 0.062 0.073 M300 12.5 13.3 12.1 13.2 TB 27.5 27.7 27.0 27.2 EB% 523 520 532 515 Thermal conductivity 0.178 0.210 0.256 0.258
[0081] Note: The DMA test conditions for tanδ / 60℃ are 151℃×30min (test conditions frequency 20Hz, strain 10±2%, temperature scan 0℃~80℃).
[0082] From the above examples, it can be seen that the reinforcing effect of SiO2 / C composite material is similar to that of white carbon black, and the heat generation of SiO2 / C composite material is similar, but the thermal conductivity is significantly improved. From the above examples, it can be seen that the rubber composition prepared by using SiO2 / C composite material has low heat generation performance and high thermal conductivity.
[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. Application of SiO2 / C composite material in high thermal conductivity base rubber of tire, characterized in that: The tire high thermal conductivity base rubber comprises the following raw materials in parts by mass: 90-110 parts of natural rubber, 0-45 parts of filler, 10-45 parts of SiO2 / C composite material, 4-10 parts of activator, 2-5 parts of vulcanizer, 2-5 parts of antioxidant, and 0.5-1.5 parts of microcrystalline wax.
2. The use of the SiO2 / C composite material as claimed in claim 1 in a high thermal conductivity base rubber of a tire, characterized in that: The filler is one or more of carbon black N220, carbon black N234, carbon black N375, carbon black N347, carbon black N339, carbon black N330, carbon black N326, carbon black N660 and pyrolysis carbon black.
3. Application of the SiO2 / C composite material as claimed in claim 1 or 2 in a high thermal conductivity base rubber of a tire, characterized in that: The preparation method of the SiO2 / C composite material comprises the following steps: (A), mixing the edible fungus cultivation body with porous silica to obtain a silica composite edible fungus cultivation body; The silicon dioxide composite edible fungus cultivation body is mixed with edible fungi to culture the edible fungi; after the culture is completed, the edible fungi are removed and the discarded cultivation body is retained; (B) carbonizing the discarded culture medium in step (A) to obtain a SiO2 / C composite material.
4. The use of the SiO2 / C composite material as claimed in claim 3 in a high thermal conductivity base rubber of a tire, characterized in that: The porous silicon dioxide is one or more of silica powder, carbon monoxide, diatomaceous earth, diatom shale, opal, zeolite and montmorillonite.
5. Application of the SiO2 / C composite material as claimed in claim 1 or 4 in a high thermal conductivity base rubber of a tire, characterized in that: The activator is one or more of stearic acid, zinc oxide, zinc stearate and lignin zinc salt.
6. The use of the SiO2 / C composite material as claimed in claim 5 in a high thermal conductivity base rubber of a tire, characterized in that: The vulcanizing agent is one or more of sulfur, accelerator NS and accelerator CZ; the antioxidant is antioxidant 4020 and / or antioxidant RD.
7. Use of the SiO2 / C composite material as claimed in claim 1, 2, 4 or 6 in a high thermal conductivity base rubber of a tire, characterized in that: The preparation method of the tire high thermal conductivity base rubber comprises the following steps: (1) mixing natural rubber, filler, SiO2 / C composite material, activator, antioxidant and microcrystalline wax to obtain a masterbatch; (2) The masterbatch and the vulcanizing agent are mixed to obtain the tire high thermal conductivity base rubber.
8. The use of the SiO2 / C composite material as claimed in claim 7 in a high thermal conductivity base rubber of a tire, characterized in that: The mixing speed in step (1) is 45-55 rpm, the mixing time is 30-50 s, the plug lifting and pressing time of the mixing is 20-30 s, and the mixing debonding temperature is 145-165°C.
9. Application of the SiO2 / C composite material as claimed in claim 8 in a high thermal conductivity base rubber of a tire, characterized in that: The mixing speed in step (2) is 25-35 rpm; the mixing time is 30-50 s, the plug lifting and pressing time of the mixing is 20-30 s, and the mixing debonding temperature is 100-113°C.
Citation Information
Patent Citations
Carbon-coated white carbon black
CN103937293A
Modified white carbon black and tread rubber thereof
CN110396226A
Bio-based compound modified white carbon black, preparation method thereof and application of bio-based compound modified white carbon black in tire production
CN117757143A
Tire rubber composition comprising silica / carbon complex
KR1020100031418A
